MULTI-LEVEL STEGANOGRAPHY SYSTEM USING WAVELET TRANSFORM - aldeen Abad Khalid, Rajaa; Ala’a Hussain, Aman (Journal of Engineering and Sustainable Development, 2018)
Sending encrypted messages frequently will draw the attention of third parties, i.e. crackers and hackers, perhaps causing attempts to break and reveal the original messages. In a digital world, steganography is introduced to hide the existence of the communication by concealing a secret message inside another unsuspicious message.The aim of this paper isto produce proposed method to provide a high level security system by implementing and designing multi-level steganography system to hide data in a color video-cover. This system is more complex system, it implemented in two levels of embedding and this is an issue of the high level of security because it required two levels of extraction to extract the hidden data. The system is implemented in the frequency domain, using wavelet transform domain. The idea of using transformation in the proposed system is due to the results of previous published works which indicated the hiding in the frequency domain is more effective than hiding in time domain, due to compactness attributes of some transforms and due to its robustness. A singular value decomposition (SVD) is also used in this proposed system. MATLAB programming environment is used to simulate the total system.